ECONOMIC RECESSION IN 7EM COUNTRIES: EVIDENCE OF 3P CAPABILITY AND IMPACT OF COVID-19 - Ade Novalina; Ramli Ramli; Murni Daulay; Dede Ruslan (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
This study aims to analyze the ability of three government policies and the strong impact of COVID-19 on the economic recession in seven emerging market countries (China, India, Indonesia, Russia, Brazil, Turkey, and Egypt). T-test and independent-sample t-test. This study resulted in the findings of the ARDL Panel model, proving that the leading indicators of state-based financial system stability are China, India, and Brazil. In contrast, the order of the top policy indicators of policy/variable financial system stability is fiscal policy (GOV), monetary policy (I.R.), and policy macroprudential (NPL). The leading indicators of state-based economic stability are Indonesia and Russia. In contrast, the order of leading indicators of policy/variable-based economic stability is macroprudential policy (LDR), fiscal policy (Tax), and monetary policy (JUB). During the Covid-19 pandemic, the effectiveness of financial system stability, apart from China, all countries experienced economic instability. On economic stability, apart from China and Turkey, all countries experienced economic instability after the Covid-19 Pandemic. Recommendation: the policies needed to control financial system stability focus on macroprudential policies and fiscal policies. In contrast, the effectiveness of the procedures necessary to maintain economic stability is through macroprudential policies.